2016
DOI: 10.1007/s00220-016-2631-x
|View full text |Cite
|
Sign up to set email alerts
|

Steady States and Universal Conductance in a Quenched Luttinger Model

Abstract: We obtain exact analytical results for the evolution of a 1+1-dimensional Luttinger model prepared in a domain wall initial state, i.e., a state with different densities on its left and right sides. Such an initial state is modeled as the ground state of a translation invariant Luttinger Hamiltonian H λ with short range non-local interaction and different chemical potentials to the left and right of the origin. The system evolves for time t > 0 via a Hamiltonian H λ ′ which differs from H λ by the strength of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 48 publications
7
90
0
Order By: Relevance
“…There, under the assumption of quasistationarity, a semiclassical picture applies where the information about the initial state is carried by free stable quasiparticles moving throughout the system. Similar results were obtained in the framework of conformal field theory and Luttinger liquid descriptions [25][26][27][28][29][30][31][32][33][34][35][36][37]. In the presence of interactions the situation was less clear [38][39][40][41][42][43][44][45][46][47], but, eventually, Refs [48,49] have shown that the continuity equations satisfied by the (quasi)local conserved quantities are sufficient to characterize the late-time behavior.…”
supporting
confidence: 71%
“…There, under the assumption of quasistationarity, a semiclassical picture applies where the information about the initial state is carried by free stable quasiparticles moving throughout the system. Similar results were obtained in the framework of conformal field theory and Luttinger liquid descriptions [25][26][27][28][29][30][31][32][33][34][35][36][37]. In the presence of interactions the situation was less clear [38][39][40][41][42][43][44][45][46][47], but, eventually, Refs [48,49] have shown that the continuity equations satisfied by the (quasi)local conserved quantities are sufficient to characterize the late-time behavior.…”
supporting
confidence: 71%
“…and the plasmon velocity v = v F 1 + 2λ/(πv F ) [36,39]. We found in [33] the following exact expectation values of the energy density and the heat current in the thermodynamic limit marked by the superscript ∞ on the expectations: 3…”
Section: Introductionmentioning
confidence: 83%
“…The evolution of the energy density and the heat current obtained in [33] permits then to better understand the shortcomings of the partitioning protocol. It also sheds a new interesting light on transport in integrable systems and, in particular, on how its universal features [35] emerge at long times for a large class of nonequilibrium initial states, see [36] and also Sect. 4.3 below for a related discussion of charge transport in the Luttinger model.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A particularly simple, yet non-trivial, setting which has been widely investigated is the so-called bipartitioning protocol, where two semi-infinite systems, initially held at different temperatures, are suddenly joined together and left to evolve unitarily under a homogeneous Hamiltonian. While this protocol is of obvious interest for the study of transport, until recently its analytic understanding was limited to the cases of free [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] or conformally invariant models [51][52][53][54][55][56][57][58][59][60][61][62]. A major breakthrough came in Refs.…”
Section: Introductionmentioning
confidence: 99%